A consensus on men's health status and policy in Asia: a Delphi survey - Teo, C.H.; Ng, C.J.; Ho, C.C.K.; Tan, H.M. (Elsevier, 2015)
Objective: There is currently no documentation on the availability and implementation of policies related to men's health in Asia. This Delphi study aimed to achieve an Asian consensus on men's health policy based on the opinions and recommendations from men's health key opinion leaders. Study design: A two-phase Delphi online survey was used to gather information from men's health stakeholders across Asian countries. Methods: All stakeholders were invited to participate in the survey through men's health conferences, personal contacts, recommendations from international men's health organizations and snowballing method. Stakeholders were asked about their concerns on 17 men's health key issues as well as their opinion on the availability and recommendations on men's health policies and programmes in their countries. Results: There were a total of 128 stakeholders (policy makers, clinicians, researchers and consumers), from 28 Asian countries, who responded in the survey. Up to 85% of stakeholders were concerned about various men's health issues in Asia and in their respective country, particularly in smoking, ischaemic heart disease and high blood pressure. There is a lack of men's health policies and programmes in Asia (availability=11.6-43.5%) and up to 92.9% of stakeholders recommended that these should be developed. Conclusions: These findings call for policy change and development, and more importantly a concerted effort to elevate men's health status in Asia.